Design and Development of a Maximum Demand Controller for Energy Efficiency in a Smart Home Environment - Vengadeshwaran Velu; Pavitra Kunasegaran; Nithiya Ruben Shanmugam (Malaysian Journal of Science and Advanced Technology, 2023)
Nowadays, number of energy efficiency measures are being implemented in the smart home environment to conserve the energy consumption. This research attempts to design and develop a solution for an effective energy consumption in a smart home environment. The microcontroller system monitors the electrical energy consumption in real time and to ensure the power consumption is within the limit or predefined maximum demand value. Once the real time power consumption reaches the pre-set value prior to reaching its maximum demand, there will be an alarm triggered to warn the user that the power consumption is about to reach the predefined value. Once the power consumption exceeds the predefined maximum demand, the connected load will be automatically switched off sequentially one by one based on the pre-planned look up table. Results obtained through simulation and practical are presented in this paper. Recommendations are given for further enhancement of the proposed design for the smart home applications.